Rancangan Album Elektronik Keberkasan Di Era Digital Menuju Good Faculty Governance (Studi Kasus : Fakultas Ilmu Komputer Universitas Esa Unggul) - Malabay Malabay; Agus Herwanto; Sawali Wahyu; Theodora Maria Putri Komul (Fakultas Teknik Universitas Hamzanwadi, 2022)
The digital era of the application of information technology continues to develop and faces the development of information technology, must be able to follow and adapt to skills and innovations in the form of support for supporting devices to produce such as the design model of an electronic album of files as governance to overcome the unorganized and unsustainable flow of files and their descriptions. as well as the situation of the availability of files for institutional or personal interests and needs that are not yet available on an ongoing basis. The Electronic Album Design for Files in the Digital Era Towards Good Faculty Governance was prepared using a strategic theme and issue approach set out in the Master Plan for Development of the Esa Unggul University and the method used was based on a descriptive qualitative approach by taking into account the study of supporting literature as a basis for discussion and observation or observations that are supported by a tiered paradigm such as the waterfall paradigm with a series of stages such as requirements to analyze complete requirements and determine software requirements then design or design through a diagram form to facilitate the implementation and integration process and system maintenance so that it can run well . With a series of stages from a waterfall paradigm, the process of forming electronic album files can be generated by utilizing a combination of storage techniques in one place and hyperlink techniques to increase work effectiveness and efficiency.